DEVELOPMENT OF PROJECT-BASED NARRATIVE READING MATERIALS - Rika Rika; Tri Purnama Nasution (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The objective of this study was to develop appropriate materials for reading narrative text. This study was carried out at English Department of Universitas Negeri Medan. This research was conducted by using Research and Development (R&D) Method. The research consists of six stages; gathering information and data, analysing data, designing materials, validating by experts, revising materials, and the last was final product. The data was gathered through the distribution of questionnaire for students and interviewed a lecturer to get the students’ need. The product has been validated by two experts in percentage terms. The average score of experts’ validations was 94.2% in content aspect, the presentation aspect was 95%, the language aspect was 96.6%, and the layout was 95%. The average score was 95.2% which categorized as very good. This study concluded that the developed project-based reading materials of narrative text may be used as teaching materials.